PENGARUH PENGAWASAN, DISIPLIN KERJA, DAN KOMPENSASI TERHADAP KINERJA KARYAWAN PADA PT. COCA COLA AMATIL INDONESIA CABANG PEKANBARU - Julita Fransiska Tambunan; Taufiqurrahman '; Tengku Firli Musfar (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2017)
The research was conducted in the PT. Coca Cola Amtil Indonesia Pekanbaru Branch. This study aims to determine how the effect of Supervision, Discipline of work, and compensation onemployees performance at PT. Coca Cola Amatil Indonesia Pekanbaru Branch.The study is a population. The number of samples in this study were 88 respondents. The method of analysis used in this study is the method of regression analysis using SPSS verson 21.0.The results showed that the variables of Supervision, Discipline Of Work, And Compensation Simultane ously significant effect on Employees performance. Further more, based on t test results partially be know that the results of the t test for variables Supervision was significantly on labor Employees performance which